2005
DOI: 10.1143/jjap.44.1225
|View full text |Cite
|
Sign up to set email alerts
|

Development and Analysis of a High-Pressure Micro Jet Pad Conditioning System for Interlayer Dielectric Chemical Mechanical Planarization

Abstract: We study deformation of N = 2 and N = 4 super Yang-Mills theories, which are obtained as the low-energy effective theories on the (fractional) D3-branes in the presence of constant Ramond-Ramond 3-form background. We calculate the Lagrangian at the second order in the deformation parameter from open string disk amplitudes. In N = 4 case we find that all supersymmetries are broken for generic deformation parameter but part of supersymmetries are unbroken for special case. We also find that classical vacua admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…HPMJ technology has been evaluated previously on polyurethane ͑Rohm and Haas IC1000͒ as well as soft pads ͑Rohm and Haas SUBA IV͒. 4,5 These studies have confirmed that HPMJ conditioning can clean the pad surface. Other studies have further shown that HPMJ results in lower ILD RRs ͑compared to diamond disk conditioning͒ as a result of slurry dilution inside and on the pad.…”
mentioning
confidence: 83%
“…HPMJ technology has been evaluated previously on polyurethane ͑Rohm and Haas IC1000͒ as well as soft pads ͑Rohm and Haas SUBA IV͒. 4,5 These studies have confirmed that HPMJ conditioning can clean the pad surface. Other studies have further shown that HPMJ results in lower ILD RRs ͑compared to diamond disk conditioning͒ as a result of slurry dilution inside and on the pad.…”
mentioning
confidence: 83%
“…The results showed that when using the HPMJ method to condition polishing pads, the same conditioning effect as the traditional conditioning can be obtained in half the processing time; moreover, the polishing pad conditioning efficiency and pad life are improved compared to the traditional method. SEIKE et al [ 21 ] studied the effect of experimental parameters such as nozzle speed on the conditioning results. Moreover, they analyzed the kinetic energy range of water droplets ejected from the HPMJ system and its effect on the surface of the polishing pad.…”
Section: Introductionmentioning
confidence: 99%
“…1) In the manufacturing process of semiconductor devices, cleaning of the devices is one of the key technologies to ensure their quality. [2][3][4] The normal way of cleaning semiconductor device has been to dip the devices in a chemical liquid, as seen in RCA clean developed by Radio Corporation of America, to remove unnecessary fine particles and films. However, as the diameters of the silicon wafers increase, a singlewafer transfer-type cleaning, in which the devices are cleaned one by one to eliminate unevenness of cleaning and to achieve the requirement for shorter process time, is being used.…”
Section: Introductionmentioning
confidence: 99%